Effectiveness and Comparison of Digital Substations Over Conventional Substations - Aashir Waleed; Umar Siddique Virk; Muhammad Tanveer Riaz; Shaikh Bilal Mehmood; Saeed Ahmad; Muhammad Rameez Javed; Ali Raza (Advances in Science, Technology and Engineering Systems Journal, 2019)
The entire electrical system is changing at an abrupt speed since its beginning. With the rapid advance of renewable energies (which are constantly subject to fluctuations), the electricity generation is distributed to countless locations. The traditional model of the unidirectional flow of electricity is leaning towards multidirectional flows. This situation needs significant changes in the transport infrastructure of the electrical power system and mode of operation. Technological advancements are making a smarter and more organized management system of electricity supply and demand. This development needs to incorporate modern communication, monitoring, and control capabilities, along with the intelligent transport, generation, and storage value chain. Digital substations integrate thousands of sensors by providing greater comfort, self-reliance, availability, and safety while at the same time reducing costs, risks, and environmental damage. Conventional power system lacks digital communication, remote monitoring & control, and consumer participation. Fiber-optic cabling in digital substations will attain not only real-time data transmission but also remote maintenance. The comparison between conventional and digital substations has also been presented in this work along with latest trends in smart protection. Electronic protection and control devices based on a microprocessor, communicating with cloud servers, will enhance the flexibility to control and monitor the digital substations. A significant amount of data generated by components in the electrical substations will allow greater sophistication of the monitoring, diagnostic, protection and optimization capabilities of the facilities. The goal for the review of said advancements is to have a smart electrical system with greater efficiency and better user experience.
Keywords: Digital substations; Intelligent electronic device; Smart grids; Grid topology; Substation